Analasis Perbandingan Pengaturan Penyelenggaraan Pendidikan Profesi Advokat Antara Indonesia dan Amerika Serikat - Mauluna, Afifah Eranie; Husodo, Jadmiko Anom (Department of the Constitutional Law, Faculty of Law Universitas Sebelas Maret, 2022)
This research aims to find out the similarities and differences in the Implementation of Advocate Professional Education between Indonesia and the United States which will be used by Indonesia in forming an ideal Advocate Professional Education in Indonesia. Advocates are regulated in Law Number 18 of 2003 concerning Advocates, but in the Law there is still confusion when the Implementation of Advocate Professional Education is carried out by Advocate Organizations in the form of multi bars which should be single bars so that there is no standardization of Advocate Professional Education. Unlike the United States, which has an established and structured Advocate Professional Education with the Model Rules for Minimum Continuing Legal Education (MCLE) made by the American Bar Association (ABA). So that this raises two questions that will be discussed in this paper with the formulation of the problem in the form of how the similarities and differences in the Implementation of Advocate Professional Education between the two countries and how the ideal form of Advocate Professional Education in Indonesia. This paper uses a normative research method with a comparative approach. Overall, there are several indicators that can be compared in the Implementation of Advocate Professional Education in the two countries and in this case Indonesia must establish an Advocate Supervisory Board to improve the quality of Advocate Professional Education in Indonesia.